Analysis of employee performance : a case study in port corporation - nazwirman, nazwirman (Jurnal Organisasi dan Manajemen, 2019)
The purpose of this study was to analyze the effect of compensation, work environment and work discipline on employee performance at Port Corporation. It is important to make decisions for managers in managing the company, especially human resources. The population of this research is all employees of the human resources division. The sampling technique uses saturated sampling, where data is collected using a survey method with a questionnaire instrument. The results showed that all variables had a positive and significant effect on employee performance, both partially and simultaneously. The results of this study confirm that port companies must pay attention to compensation, work environment and work discipline if it expect superior performance of its employees.